The use of local structural similarity of distant homologues for crystallographic model building from a molecular‐replacement solution. Issue 3 (5th March 2020) - Chojnowski, Grzegorz; Choudhury, Koushik; Heuser, Philipp; Sobolev, Egor; Pereira, Joana; Oezugurel, Umut; Lamzin, Victor S.
Abstract : A novel method for the enhancement of automated protein model building using polypeptide fragments of homologous structures is presented. Abstract : The performance of automated protein model building usually decreases with resolution, mainly owing to the lower information content of the experimental data. This calls for a more elaborate use of the available structural information about macromolecules. Here, a new method is presented that uses structural homologues to improve the quality of protein models automatically constructed using ARP / wARP . The method uses local structural similarity between deposited models and the model being built, and results in longer main‐chain fragments that in turn can be more reliably docked to the protein sequence. The application of the homology‐based model extension method to the example of a CFA synthase at 2.7 Å resolution resulted in a more complete model with almost all of the residues correctly built and docked to the sequence. The method was also evaluated on 1493 molecular‐replacement solutions at a resolution of 4.0 Å and better that were submitted to the ARP / wARP web service for model building. A significant improvement in the completeness and sequence coverage of the built models has been observed.